Vận dụng lí thuyết phê bình sinh thái vào dạy học đọc hiểu văn bản thơ trong bài “Vẻ đẹp của thơ ca” ở sách giáo khoa Ngữ văn 10, Bộ Kết nối tri thức với cuộc sống - Phan , Thị Hồng Xuân; Lê , Thanh Huyền (Tạp chí Giáo dục, 2024)
Ecocriticism is the study of the relationship between literature and the natural environment. The application of this theory in teaching reading comprehension aligns with the goal of helping students develop qualities and competence. This represents a proper, humane, and profound educational direction. However, in current teaching practices, both teachers and students often find it challenging to apply this new theory to teaching reading comprehension, especially the theory of ecocriticism. This article proposes a process and measures to apply Ecocriticism to teaching reading comprehension of poetry in the chapter “The Beauty of Poetry” in the Literature 10 textbook, which is part of the “Connecting Knowledge with Life” program. The research results serve as a suggestion for the direction of applying ecocritical theory to teaching reading comprehension of literary texts in schools today.